PENGOLAHAN LIMBAH CAIR BENGKEL DENGAN MENGGUNAKAN GREASE TRAP DAN FITOREMEDIASI - Yayok Suryo Purnomo; Fitria Dwi Wijayanti (EnviroUS, 2021)
Workshop liquid waste contains oil and grease, COD, and BOD. Therefore, it is necessary to carry out further processing so that this waste is not harmful to the environment if discharged into water bodies. One of the processes to process fatty oil is by using a grease trap. Meanwhile, to process COD and BOD, phytoremediation can be used. Some plants that were considered capable of reducing COD and BOD levels were water hyacinth and pistia. In this research, grease trap treatment was used and followed by phytoremediation using water hyacinth and pistia. This research found that the variation of the 9-hour sampling time in the grease trap can reduce fatty oil by 84.62%. For processing with phytoremediation, it can be concluded that water hyacinth plants were more able to reduce COD and BOD than pistia. In this study, it was found that the most effective was the variation of the sampling time of 25 days. In a reactor with ten sticks of water hyacinth was able to reduce COD by 77.82% and BOD by 83.68%, while the reactor with ten sticks of pistia was able to reduce COD by 74.48% and BOD of 67.22%.